THE IMPACT OF GOOD CORPORATE GOVERNANCE, LEVERAGE AND FIRM SIZE ON EARNINGS MANAGEMENT: EVIDENCE FROM INDONESIAN MANUFACTURING FIRMS - Laeli, Dian Nur; Fauzi, Achmad; Indriani, Susi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
The purpose of this study is to ascertain how effective corporate governance, leverage, and firm size affect earnings management in 2023 for consumer goods manufacturing businesses as well as textile and apparel subsectors that are listed on the Indonesia Stock Exchange (IDX). Purposive sampling, which selects samples based on predetermined criteria, was employed in this study. The samples were 43 manufacturing companies in the consumer goods sector, as well as textile and garment sub-sectors and components that satisfied 5 predetermined sample criteria. Based on the results, institutional ownership has no significant effect on earnings management, while independent commissioners, leverage, and firm size have a significant influence on earnings management. Institutional ownership, independent commissioners, leverage, and firm size have a significant effect on earnings management. These research findings enrich academic and practical references regarding the determinants of earnings management in the manufacturing industry listed on the IDX.